2013
DOI: 10.1002/glia.22551
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor‐β1 primes proliferating adult neural progenitor cells to electrophysiological functionality

Abstract: The differentiation of adult neural progenitors (NPCs) into functional neurons is still a limiting factor in the neural stem cell field but mandatory for the potential use of NPCs in therapeutic approaches. Neuronal function requires the appropriate electrophysiological properties. Here, we demonstrate that priming of NPCs using transforming growth factor (TGF)-β1 under conditions that usually favor NPCs' proliferation induces electrophysiological neuronal properties in adult NPCs. Gene chip array analyses rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…At the same time, we demonstrate here that TGF‐β1 reduces cell death in neurospheres and promotes the expression of neuronal‐specific gene DCX and the electrophysiological functionality of NPCs in the presence of EGF and FGF. The latter was confirmed by a more detailed electrophysiology study demonstrating the TGF‐β1 primed neural progenitors under proliferation conditions to functional maturation with firing action potentials . In summary, TGF‐β1 is promoting neuronal differentiation/survival as well as neural stem cell quiescence.…”
Section: Discussionmentioning
confidence: 70%
“…At the same time, we demonstrate here that TGF‐β1 reduces cell death in neurospheres and promotes the expression of neuronal‐specific gene DCX and the electrophysiological functionality of NPCs in the presence of EGF and FGF. The latter was confirmed by a more detailed electrophysiology study demonstrating the TGF‐β1 primed neural progenitors under proliferation conditions to functional maturation with firing action potentials . In summary, TGF‐β1 is promoting neuronal differentiation/survival as well as neural stem cell quiescence.…”
Section: Discussionmentioning
confidence: 70%
“…A similar dual role during adult neurogenesis has already been suggested for TGF-β1 [32]. We have recently demonstrated that treatment of adult neuronal progenitor cells with TGF-β1 increased LTCC activity in these cells [53]. Moreover, TGF-β1 elevated Cav1.3 mRNA expression in cerebellar granular neurons in vitro [54].…”
Section: Discussionmentioning
confidence: 84%
“…Besides, it is well documented that TGF-beta1 could alter the expression of many different integrins, cell adhesion molecules, extracellular matrix and other factors important for cellular migration and, in addition, exerts growth-inhibitory responses in normal cells, but induces migration and invasion of neoplasms [58]. Also, TGF-beta1 blocks proliferation of neural progenitor cells and promotes stem cell quiescence and neuronal survival / differentiation [36,59]. Our present study supports the hypothesis that TGF-beta1 might be a crucial factor regulating the migration of DCX positive neuroblast, as we have noticed the appearance of pSmad2 in the nucleus of DCX positive neuroblasts in the RMS of WT rats and also in the striatum of tgHD rat.…”
Section: Discussionmentioning
confidence: 99%